An injectable collagen-genipin-carbon dot hydrogel combined with photodynamic therapy to enhance chondrogenesis. (October 2019) - Lu, Zhenhui; Liu, Sijia; Le, Yiguan; Qin, Zainen; He, Mingwei; Xu, Fuben; Zhu, Ye; Zhao, Jinmin; Mao, Chuanbin; Zheng, Li
Abstract: Collagen has been widely used for cartilage repair, but its low stiffness and rapid degradation disfavor chondrogenesis. Here we conjugated biocompatible carbon dot nanoparticles (CD NPs) onto collagen through a natural product crosslinker (genipin) to prepare an injectable hydrogel (termed collagen-genipin-CD nanoparticles, CGN). The CGN hydrogel showed increased stiffness due to the cross-linking effect of genipin and the presence of CD NPs, and could produce a moderate amount of reactive oxygen species (ROS) by photodynamic therapy (PDT). Both the stiffness enhancement and ROS generation resulted in improved chondrogenic differentiation of bone marrow-derived stem cells (BMSCs) and the subsequent enhanced cartilage regeneration for cartilage defect repair. Specifically, the CGN hydrogel presented a 21-fold higher compression modulus and a 39.3% lower degradation rate than the pure collagen hydrogel. A combination of both PDT and CGN hydrogel increased the BMSCs proliferation by 50.3%, upregulated their expression of cartilage-specific genes by multiple folds, and enhanced GAG secretion by 205.1% on day 21. This combination also accelerated the cartilage regeneration within as short as 8 weeks. The stiffness enhancement and ROS generation synergistically contributed to chondrogenic differentiation by regulating the TGF-β/SMAD and mTOR signaling pathway, respectively. The combination of CD-modified hydrogel injection and PDT treatment represents a new strategy for minimally invasive repair of cartilage defects.